"Owning one's story is as important as the ownership of physical space": An Interview with Susan Abulhawa. (1st January 2019) - Qabaha, Ahmad
Abstract : In this interview, American-Palestinian writer, political commentator and human rights activist Susan Abulhawa, author of Mornings in Jenin (2006), My Voice Sought the Wind (2013) and The Blue Between Sky and Water (2015), discusses why it is important for Palestinians to reciprocate solidarity with other social justice struggles and the ways in which she engages with the notions of strangeness and exile in her fiction. Abulhawa also comments on the human, cultural and communal aspects of her work, as well as the relationship between literature, especially the novel, history and politics.